Two-period supply chain with flexible trade credit contract. (30th December 2016) - Yang, Honglin; Zhuo, Wenyan; Zha, Yong; Wan, Hong
Highlights: We consider a fully flexible trade credit contract in a two-period supply chain. We design an incentive of a discounted wholesale price for the early payment. We propose a continuous newsvendor model to analyze the optimal decisions. Abstract: This paper studies a two-period supply chain that consists of a retailer and a supplier. A newsvendor-like retailer is capital constrained and orders products using a supplier's trade credits to satisfy uncertain market demand. Most existing studies show that the retailer always postpones payment until the due date. To recall the loans earlier, we present a case in which the supplier, as a Stackelberg leader, offers an incentive of a discounted wholesale price in the second order to entice the retailer to choose flexible early payment. The proposed incentive is related to the retailer's early payment time in the first period. In the presence of bankruptcy risks for both the retailer and supplier, we propose a continuous newsvendor model of a two-period supply chain to analyze the decisions involved in the flexible trade credit contract. The analytic forms confirm that such an incentive can improve the decentralized supply chain efficiency and decreases the supplier's trade credit risk. The retailer always prefers early payment to payment around the due date to increase revenues. Furthermore, the action of paying early might help the retailer adjust cash flow between the two periods. We also find that a revenue sharing contract significantly affects the retailer's payment behavior and supplier's wholesale price. The numerical simulations support our results.